Hulk : the abomination! - Raicht, Mike (The Hulk series, 2006)
Dr. Bruce Banner, a scientist who turns into the Hulk whenever he is provoked, heads for Texas after seeing a news report that a green monster is terrorizing the state, and finds Bionsky, a former colleague who tried to continue Banner's work with gamma radiation and only succeeded in turning himself into a monster.